Myocardial revascularization: do age and sex matter? - Davierwala, Piroze M.; Mohr, Friedrich W. (Journal of Thoracic Disease, 2016)
The World Health Statistics 2016, which is World health Organization’s annual compilation of health statistics for its 194 Member States, reported that the global average life span has dramatically increased by 5 years since 2000, making it the fastest rise since the 1960s (1). Globally, a 151% surge is expected in the population ≥85 years between 2005 and 2030, compared to an increase of only 104% in those aged ≥65 years (2). The American Heart Association predicts a significant rise in the burden of cardiovascular disease in the USA by 2030 due to this rise in the aging population (3). Approximately 25% of the population >75 years suffers from symptoms of cardiovascular diseases (4) and has resulted in a demographic shift in patients with coronary artery disease (CAD) requiring myocardial revascularization. The mean age of patients undergoing cardiac surgery increased from 55.8 years in 1990 to 68.8 years in 2007, of which, 9.8% were octogenarians (5). The healthcare challenges and clinical decision-making in elderly patients are real concerns in daily practice as they often present with several comorbidities existing concurrently, which not only complicates management of CAD, but also leads to development of newer disease states or worsening of preexisting conditions (6). Additionally, factors such as frailty, sarcopenia and cognitive decline, which are unique to the geriatric population, frequently compound multimorbidity management and cause a hindrance to smooth postoperative recovery and rehabilitation despite uneventful procedures (7). Furthermore, such factors reduce the reserve capacity and strength of elderly patients to recover, sometimes, even from minor set-backs or complications.